Implementation of the Distribution of Social Assistance to Communities Affected by Covid-19 in Village Based on the Minister of Social Affairs Regulation Number 20 of 2019 concerning the Distribution of Non-Cash Food Aid - Ira Sanjaya; Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2023)
That is Peremensos 20 of 2019 concerning B.P.N.T which was launched by the government to deal with poverty. This programs is a substitut for the poor rice proyect which aim to increase food securiti & support balance nutrision for K.P.M, increase the level of targeting accurate and the time of reciving food assistance for recipient families. Ketimang, Kec. Wonoayu is one of the villages that has implemented the latest governmen projec, name is Non-Cash Food Aid. the purpose of writing this scientific paper is to see the implementation and description of how the implementation of the Non-Cash Food Aid distribution progrms in Ketimang during the Covid pandemic. The method chosen by the author is descriptive qualitatife. Data collection techniques through question and answer & field observations. Data analysis techniq, data presentattion & draw conclusions. The results of the study illustrate that implementasion of the social assist project in Ketimang country has been in acordance with the technical guidelines for the 2021 B.PN.T progrm. Although in the distribusion process there is still some problems, such as the lack of socializattion to the communitty, especialy the original KPM. Howeer, this has a good impact and benefit for the wellfare of the communiti, specially KPM.